Gender Bias in Translation Using Google Translate: Problems and Solution - Fitria, Tira Nur (Language Circle: Journal of Language and Literature, 2021)
This study discusses gender bias in terms of language especially from Indonesian into English translation by using Google Translate. This research is descriptive qualitative research. The result shows that most likely every language has gender-biased sides, including English because the type of society in the reality of life is more represented by men and women. In Google translate, the unequal differences between men and women translated into google translate causes the system to be considered biased and sexist towards gender. Whereas in fact, nowadays all genders can have various activities and jobs. Indonesian is also a gender-neutral language. When google translates to change into English, the sentence becomes gendered. The Indonesian language in this case seems to have been saved from being sexist because it does not associate a particular profession or activity with any gender. Unlike English, which adjusts personal pronouns based on gender. Google Translate is not always accurate, especially when translating from English to other languages. That is where Google Translate tends to go astray. The problem is that many languages have gender-based words, whereas English does not. But some words, like profession or occupation, can be masculine or feminine depending on the subject of the sentence, by assigning gender to certain adjectives and words that describe them. Equality in gender and race has been very difficult to achieve in machine technology situations because these systems are trained on existing content, and are not demographically representative. Google decided to make changes. It is important to adapt and build technology that can better serve humans. What may seem like small changes to everyday life are big steps towards gender equality. The way people speak their respective languages is one of the strongest ways of gender discrimination.